Planetary specters : race, migration, and climate change in the twenty-first century - Ahuja, Neel, 1980- (The University of North Carolina Press, 2021)
"Neel Ahuja traces the development of "climate migrant" discourses in public media and policy over the past decade, arguing that journalists, security experts, politicians, and NGOs have often oversimplified climate change and obfuscated the complex processes that have led to mass and supposedly environmental-change driven migration. To understand the systemic reasons for mass migration, Ahuja argues, it is necessary to reframe climate disaster as interlinked with the history of capitalism and the global politics of race, wherein climate change exacerbates existing issues such as land displacement, labor exploitation, debt finance, and pollution"--